(untitled) (University Journal of Zoology, Rajshahi University, 2010)
The study was aimed at standardization of cryopreservation protocol for the common carp, (Cyprinus carpio) spermatozoa for using in the artificial propagation. Three extenders (Alsever’s solution, egg-yolk citrate and 0.9% NaCl) were combined with three cryoprotectants (ethanol, methanol and DMSO). Two-step freezing protocol (5°C to -4°C at a rate of 4°C per minute then -4°C to -80°C at a rate of 10°C per minute and finally held for 10 min) was carried out in a computer-controlled freezer where 0.25 ml straws containing spermatozoa were stored in a liquid nitrogen container at -196°C. Alsever’s solution with ethanol, Alsever’s solution with methanol and egg yolk citrate with DMSO gave better motility (%) in both pre-freeze (93.33±1.05, 90±1.83 and 88.33±2.11, respectively) and post-thaw (80±4.28, 74.17±3.96 and 76.67±4.59, respectively) periods whereas, 10% cryoprotectant gave the best motility during post-thaw period. Considering both pre-freeze and post-thaw motilities of the common carp spermatozoa, 1:9 was the best ratio for the milt and cryodiluents. The egg yolk citrate with DMSO yielded the best fertilization (37.67±1.76%) and hatching (28.67±1.85%) compared to other combinations under study. Key words: Cyprinus carpio; spermatozoa; cryopreservation; cryoprotectant; cryodiluent; fertility. DOI: 10.3329/ujzru.v28i0.5287 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 51-55